Molecular detection and phylogeny of Ehrlichia canis and Anaplasma platys in naturally infected dogs in Central and Northeast Thailand - Andaman Purisarn; Sakulchit Wichianchot; Cherdsak Maneeruttanarungroj; Bandid Mangkit; Wuttinun Raksajit; Sarawan Kaewmongkol; Thitichai Jarudecha; Wanat Sricharern; Rucksak Rucksaken (Veterinary World, 2022)
Background and Aim: genes. Materials and Methods: genes. All positive PCR amplicons were sequenced, and phylogenetic trees were constructed based on the maximum likelihood method. Results: sequences were clearly grouped into their own clades. Conclusion: were related to prior Thai strains and those from other countries.
Keywords: Vector-borne infectious diseases; Rabies epidemiology and control; Viral Infections and Vectors